Prediction of Gut Wall Integrity Loss in Viral Gastroenteritis by Non-Invasive Marker - Elnady, Hala G. (Open Access Maced J Med Sci, 2015)
BACKGROUND: Intestinal fatty acid binding proteins (I-FABPs) are mainly expressed in the intestinal villi, which are the initial site of destruction in viral gastroenteritis. AIM: This study was designed to assess serum I-FABPs as a predictor of gut wall integrity loss in viral gastroenteritis. PATIENTS AND METHODS: This case-control cross-sectional study was conducted on 93 cases of acute viral gastroenteritis. Twenty-eight healthy children matching in age were recruited as control group. Serum I-FABPs were measured using ELISA technique. Viral detection and typing were done by PCR for adenovirus, and by Reverse transcriptase PCR for rotavirus, astrovirus and norovirus. RESULTS: Serum I-FABPs level was significantly higher in the cases compared to the controls and was also higher in the 46 rotavirus gastroenteritis cases compared to other viral gastroenteritis cases. Serum I- FABPs level was significantly higher in severely dehydrated cases as compared to mildly dehydrated ones (P=0.037). CONCLUSION: Serum I-FABPs could be used as an early and sensitive predictor marker of gut wall integrity loss in children with viral gastroenteritis and its level can indicate case severity.